Purification and Characterization of a Novel Factor of Crotoxin Inter-CRO (V-1), a New Phospholipase A2 Isoform from Crotalus durissus collilineatus Snake Venom Using an In Vitro Neuromuscular Preparation - Vera-Gonzales, Corina (2022)
The fractionation of Crotalus durissus collilineatus whole venom through an HPLC chromatographic method enabled the purification of a new V-1 neurotoxin. Inter-CRO (V-1) presents similarity in its primary structure to crotoxin B (CB), suggesting another isoform of this toxin. The aim of this study was to compare V-1 to the crotoxin complex (CA/CB) and CB to elucidate aspects related to its functionality. The homogeneity of the purified protein was confirmed with a molecular mass of 1425.45 Da, further verified by mass spectrometry. The sequence of the protein showed high similarity to other viperid snake venom PLA2 proteins. The results of this study report that V-1 is an uncharacterized novel toxin with different biological activities from CB. V-1 maintained catalytic activity but presented neurotoxic activity as observed by the 2.5-fold increase in twitch tension record compared to control values on isolated muscle cells. View Full-Text